Incidental pancreatic lipomas diagnosed by computed tomography - Hasbahçeci, Mustafa; Erol, Cengiz; Başak, Fatih; Barman, Ahmet; Şeker, Mehmet Metin (AVES, 2014)
Objective: Fatty tumours of the pancreas are rarely reported. With the advent of the imaging techniques, diagnosis of such tumours based on radiologic imaging is increasing. Materials and Methods: Between June 2006 and June 2012, four patients with pancreatic lipomas that were diagnosed by computed tomography were reviewed retrospectively with regard to their imaging findings. There were 3 male and one female patient with a mean age of 60.8 years (from 53 to 67 years). Results: A single well-bordered nodular fatty lesion with well-delin- eated thin homogeneous capsule was seen in all patients. The mean densitometric measurement of the lesions was -76 Hounsfield units (HU) (from -83 HU to -63 HU). The size of the lesions was from 7 mm to 12 mm with a mean of 8.75mm. They were located in the tail, body and neck of the pancreas in two, one and one patient, respectively. There was no associated pancreatobiliary pathology. Histopathologic evaluation was not planned because of their incidental diagnosis in these asymptomatic patients. Conclusion: Pancreatic lipomas are silent lesions, incidentally found during imaging procedures. They have specific computed tomography findings and do not require any additional diagnostic imaging.

Amaç: Pankreasın yağlı tümörleri nadiren bildirilmektedir. Görüntüleme yöntemlerinin yaygınlaşması ile bu tür tümörlerin radyolojik görüntüleme temelli tanısı giderek artmaktadır. Gereç ve Yöntem: Haziran 2006-2012 dönemi arasında bilgisayarlı tomografi ile tanı konulan pankreas lipomlu dört hasta, görüntüleme bulguları açısından retrospektif olarak değerlendirildi. Ortalama yaşı 60.8 yıl (değer aralığı 53-67 yıl) olan 3 erkek ve bir kadın hasta vardı. Bulgular: Hastaların tamamında, ince homojen kapsüllü ve düzenli sınırlı nodüler yağlı tek bir lezyon görüldü. Ortalama densitometrik ölçüm değeri -76 Hounsfield ünitesi (HU) (değer aralığı -83 ile-63 arası) idi. Lezyonların büyüklüğü 7 ile 12 mm arası (ortalama 8,75 mm) değişiyordu. İki hastada kuyrukta olmak üzere, diğerleri gövde ve boyun bölgesi yerleşimli idi. Eşlik eden pankreatobiliyer patoloji yoktu. Asemptomatik hastalarda rastlantısal tanı nedeniyle, histopatolojik inceleme planlanmadı. Sonuç: Pankreas lipomları görüntüleme yöntemleri esnasında rastlantısal olarak görülen sessiz lezyonlardır. Spesifik tanısal bulguları olması nedeniyle ilave girişimlere ihtiyaç yoktur.
Bilgisayarlı tomografi ile tanısı konulan rastlantısal pankreas lipomları
Keywords: Pancreas; Lipoma; Computed Tomography; Diagnosis; Pankreas; Lipom; Bilgisayarlı Tomografi; Tanı